The Effect of ACE Inhibitors/ARBs Withdrawal on the Risk of Postoperative Complications in Abdominal Surgery - N. V. Trembach; M. A. Magomedov; V. G. Krasnov; L. Yu. Chernienko; S. N. Shevyrev; A. S. Popov; E. V. Tyutyunova; S. N. Vatutin; A. A. Dmitriev; V. V. Fisher; E. V. Volkov; I. V. Yatsuk; et al. (Общая реаниматология)
A significant proportion of patients undergoing non-cardiac surgery receive therapy with angiotensin converting enzyme (ACE) inhibitors/angiotensin II receptor blockers (ARBs), which are usually prescribed for treatment of arterial hypertension and CHF. Current guidelines fail to provide clear consensus on whether it is worth discontinuing ACEi/ARBs before non-cardiac surgery. The aim of this research was to assess the contribution of pre-op ACEi/ARBs withdrawal to the development of postoperative complications in patients after abdominal surgery using data from STOPRISK database.Materials and methods. Data of 1945 patients from of the STOPRISK database was used for the analysis. Patients were retrospectively divided into two groups: first group (N=471, 24.2%) included patients subjected to ACEi/ARBs withdrawal 24 hours before surgery, second group (N=1474, 75.8%) included patients continuing on ACEi/ARBs therapy. The 30-day outcomes were analyzed — postoperative complications (acute kidney injury, acute respiratory distress syndrome, anastomosis failure, arrhythmias, circulatory arrest, cardiogenic pulmonary edema, postoperative delirium, myocardial infarction, pneumonia, ileus, postoperative bleeding, pulmonary embolism, acute cerebrovascular accident, wound infection) and mortality. We were not evaluating intraoperative and postoperative arterial hypotension and hypertension, we analyzed the use of vasopressors as a surrogate marker. ACEi/ARBs re-initiation after surgery was not evaluated.Results. One or more post-operative complications were documented in 113 patients (5.8%). Only postoperative delirium was more common in patients (1.06% vs. 0.27%, P=0.027) after ACEi/ARBs withdrawal 24 hours before surgery, the difference reached statistical significance. Sub-analysis in the group of patients with arterial hypertension as the only comorbidity showed no statistically significant differences in the outcomes. Sub-analysis in the group of patients with CFH showed higher incidence of postoperative delirium after ACEi/ARBs withdrawal (2.68% vs. 0.6%, P=0.023). The logistic regression analysis showed that the risk of developing postoperative delirium is influenced by age, vasopressor support, and ACEi/ARBs withdrawal (the area under the curve for the model was 0.92 (0.90–0.93).Conclusion. Rates of pre-op ACEi/ARBs withdrawal (24.2%) are consistent with published data. In the entire cohort, ACEi/ARBs withdrawal resulted in higher incidence of postoperative delirium, as well as in the subgroup of patients with CHF, while ACEi/ARBs withdrawal in the subgroup of patients with arterial hypertension had no influence on postop complications.ACEi/ARBs withdrawal, along with hemodynamic instability and older age, contributes to the development of postoperative delirium, which is the subject of future research.